Pulmonary Delivery of Triptorelin Loaded in Pluronic Based Nanomicelles in Rat Model - Vakilzadeh, Hamed; Varshosaz, Jaleh; Minaiyan, Mohsen (Current Drug Delivery, 2018)
Introduction: Triptorelin, the synthetic analog of gonadotrophin-releasing hormone, is used for the treatment of sex hormone dependent diseases via parenteral administration. The aim of the present study was to investigate the possibility of triptorelin pulmonary delivery and preparation of a pulmonary nanocarrier delivery system for it. Methods: Triptorelin was loaded in Pluronic-F127 grafted poly (methyl vinyl ether-alt-maleic acid) nanomicelles by direct dissolution method. Effects of the processing variables including: drug/polymer ratio, temperature, stirring rate and time on the physicochemical properties of nanomicelles including zeta potential, particle size, drug entrapment efficiency and release profiles of triptorelin loaded nanomicelles were evaluated. For animal studies 24 Wistar rats were separated into four groups of six. Group 1 received blank nanomicelles, groups 2, 3 and 4 were treated with a single dose of 250 μg.kg-1 of triptorelin solution subcutaneously (sc), pulmonary spraying of triptorelin solution (250 μg.kg-1) and pulmonary spraying of triptorelin nanomicelles (250 μg.kg-1), respectively by microsprayer. Results: The optimized micelles had particle size of 87.35 nm, zeta potential of -12.8 mV, entrapment efficiency of 84.36% and release efficiency of 65%. The area under the blood testosterone levels increment differed significantly (p<0.05) between pulmonary triptorelin nanomicelles and drug solution. The pharmacological activity of the simple solution was 59.38%, while it was 80.18% for the nanomicelles relative to sc route of administration with prolonged residence time. Conclusion: The results of this study show that not only triptorelin is absorbable from the lungs but also nanomicelles can significantly enhance its pulmonary absorption compared to its simple solution.
Keywords: pulmonary absorption